THE REPRESENTATION OF FUNCTIONS BY WALSH DOUBLE SYSTEM IN WEIGHTED $ L_{μ}^{p} [0,1)^2 $-SPACES - Simonyan, L.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
In this work we construct a weighted space $ L_{μ}^{p},\ p ≥ 1 $, in which functions with the norm of that space are presented by Walsh double series, which coefficients are monotone in all ways.
Keywords: weighted space; Walsh double system; weight function